Leveraging Applications of Formal Methods, Verification, and Validation : 6th International Symposium, ISoLA 2014, Corfu, Greece, October 8-11, 2014 and 5th International Symposium, ISoLA 2012, Heraklion, Crete, Greece, October 15-18, 2012, Revised Selected Papers /: 6th International Symposium, ISoLA 2014, Corfu, Greece, October 8-11, 2014 and 5th International Symposium, ISoLA 2012, Heraklion, Crete, Greece, October 15-18, 2012, Revised Selected Papers. (2016) - Lamprecht, Anna-Lena
No abstract available